2014
DOI: 10.3390/molecules190915180
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Leishmanicidal Activity and Theoretical Evaluations of a Series of Substituted bis-2-Hydroxy-1,4-Naphthoquinones

Abstract: A series of eight substituted bis-2-hydroxy-1,4-naphthoquinone derivatives was synthesized through lawsone condensation with various aromatic and aliphatic aldehydes under mild acidic conditions. The title compounds were evaluated for antileishmanial activity in vitro against Leishmania amazonensis and Leishmania braziliensis promastigotes; six compounds showed good activity without significant toxic effects. The compound with the highest activity was used for an in vivo assay with Leishmania amazonensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
0
29
0
3
Order By: Relevance
“…The reaction seems to be sensitive to the amount of acid and β-alanine, however, all the reactions with excess acid catalysis results in the formation of the bis-adduct dimer of lawsone, a polar product visible by TLC inspection that was studied in a previous article by our group. 23 We chose to compare this modification of the original Kopanski procedure (named method A, entry 3), with this new method B (entry 9, Table 3) in a series of experiments conducted to verify the scope of the method with a range of suitable aldehydes. These results are shown in Table 4, and we planned to submit initially the available propionaldehyde (3a), n-butyraldehyde (3b), n-valeraldehyde (3c), phenylacetaldehyde (3e), n-hexanaldehyde (3p), isobutyraldehyde (3g), isovaleraldehyde (3i) and 2-ethylbutyraldehyde (3j) to condense with lawsone (2) using both conditions A and B that differ only by B using twice the amount of catalyst that A uses ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The reaction seems to be sensitive to the amount of acid and β-alanine, however, all the reactions with excess acid catalysis results in the formation of the bis-adduct dimer of lawsone, a polar product visible by TLC inspection that was studied in a previous article by our group. 23 We chose to compare this modification of the original Kopanski procedure (named method A, entry 3), with this new method B (entry 9, Table 3) in a series of experiments conducted to verify the scope of the method with a range of suitable aldehydes. These results are shown in Table 4, and we planned to submit initially the available propionaldehyde (3a), n-butyraldehyde (3b), n-valeraldehyde (3c), phenylacetaldehyde (3e), n-hexanaldehyde (3p), isobutyraldehyde (3g), isovaleraldehyde (3i) and 2-ethylbutyraldehyde (3j) to condense with lawsone (2) using both conditions A and B that differ only by B using twice the amount of catalyst that A uses ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Fakat leishmaniasisin kemoterapisinde kullanılan bu ilaçların etkileri oldukça sınırlıdır. Ayrıca bu ilaçların çoğunun nefrotoksik, hepatotoksik ve teratojenik etkiler başta olmak üzere ciddi yan etkileri bulunmaktadır [3,9,10] . Dünyada ve Türkiye'de KL ve VL'in tedavisinde birincil ilaç olarak kullanılan beş değerli antimon türevleri, sodyum stiboglukonat (Pentostam®) ve megluminantimoniat (Glucantime®) 1940 yılında geliştirilmiş, ancak bu ilaçlara karşı direnç geliştiği, araştırıcılar tarafından bildirilmiştir [6,[11][12][13][14] .…”
Section: Hidrazon Yapısındaki On Farklı Bileşiğin Antileishmanialunclassified
“…Hastalığa karşı etkili bir profilaktik aşının bulunmaması, mevcut kullanılan ilaçların toksik etkileri ve bu ilaçlara karşı direncin giderek artması nedeniyle yeni terapötik ajanların keşfedilmesi ve geliştirilmesine öncelik verilmesi gerektiği bildirilmiştir [10,15] . Antiparaziter tedavilerde kullanılan hidrazon türevi bileşikler; aldehit veya ketonların, hidrazin veya alkilhidrazinler ile kondansasyon reaksiyonunun sonucunda sentez edilen ve kimyasal yapısı (-C=N-NH-) grubu olan bileşik sınıfının genel adıdır.…”
Section: Hidrazon Yapısındaki On Farklı Bileşiğin Antileishmanialunclassified
See 1 more Smart Citation
“…10 However, the effects of these medications are limited and there are serious side effects including nephrotoxic, hepatotoxic and teratogenic effects. 11,12 Globally and in Turkey, it has been reported that resistance has developed to the primary medication for treatment of CL and VL of five valuable antimony species, sodium stibogluconate (Pentostam®) and megluminantiamoniate (Glucantime®). [12][13][14][15][16] Due to the lack of an effective prophylactic against the disease, the toxic effects of currently-used medications and the increasing resistance to these medications, the necessity for discovery and development of new therapeutic agents has been reported.…”
Section: Introductionmentioning
confidence: 99%